1989
DOI: 10.1007/bf01313878
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus detection using probes from the 5′ and 3′ end of the genome

Abstract: This study investigated the abilities of cDNA probes from the 5' and 3' ends of the genome of human rhinoviruses (HRV-) 14, 9, and 1B to detect RNA from 59 rhinovirus serotypes. The results show that probes from the 5' end of the genomes of HRV-14, 9, and 1 B detected a large number of serotypes but the detection rate was variable and depended on the degree of homology with the particular probe. In contrast, all the 3' end probes were specific for the homologous virus. However, a long HRV-9 probe detected a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The specificity of our cDNA rhinovirus probes has been extensively established with regards to reaction with nucleic acids obtained from other viruses and human cells (Al-Nakib et al, 1986Forsyth et al, 1989). Furthermore, in this study, all serial nasal washing samples obtained from volunteers infected with coronavirus 229E-like virus and which contained coronavirus as demonstrated by virus isolation and RNA hybridization were consistently negative for rhinovirus RNA by ISH.…”
Section: Discussionsupporting
confidence: 57%
“…The specificity of our cDNA rhinovirus probes has been extensively established with regards to reaction with nucleic acids obtained from other viruses and human cells (Al-Nakib et al, 1986Forsyth et al, 1989). Furthermore, in this study, all serial nasal washing samples obtained from volunteers infected with coronavirus 229E-like virus and which contained coronavirus as demonstrated by virus isolation and RNA hybridization were consistently negative for rhinovirus RNA by ISH.…”
Section: Discussionsupporting
confidence: 57%
“…Molecular biological methods. Initial attempts at diagnosis using cDNA probes from the 5' and 3' non-coding regions were disappointing due to poor binding to a large number of serotypes [41]. Given the marked sequence variations between different serotypes in this region (Fig.…”
Section: Diagnosismentioning
confidence: 99%
“…Culturing the virus and serotyping by conventional methods [3,9] is both time consuming and, in some cases, very difficult due to the poor growth of some serotypes in tissue culture systems. It has been shown that eDNA probes complementary to the 3' end of a rhinovirus genome can bind very specifically [4] and a bank of such probes could presumably be used to type a virus, although a large panel of reagents would be required. We have recently applied the polymerase chain reaction (PCR) to the detection of rhinoviruses in clinical samples I-5, 6] and showed that in principle, one pair of oligonucleotides can be used for any rhinovirus.…”
mentioning
confidence: 99%